Production of acrylic acid through nickel-mediated coupling of ethylene and carbon dioxide - A DFT study - Graham, D.; Mitchell, C.; Bruce, M.; Metha, G.; Bowie, J.; Buntine, Mark (ACS Publications, 2007)
The production of acrylic acid (CH2=CHCO2H) via homogeneous nickel-mediated coupling of ethylene (CH2=CH2) and carbon dioxide (CO2) is industrially unattractive at present due to its stoichiometric, rather than catalytic, reaction profile. We utilize density functional theory (DFT) to describe the potential energy surface for both the nickel-mediated coupling reaction and an intramolecular deactivation reaction reported to hinder the desired catalytic activity. The calculated route for the catalytic production of acrylic acid can be divided into three main parts, none of which contain significantly large barriers that would be expected to prohibit the overall catalytic process. Investigation of the catalyst deactivation reaction reveals that the proposed product lies +102.6 kJ mol(-1) above the reactants, thereby ruling out this type of pathway as the cause of the noncatalytic activity. Instead, it is far more conceivable that the overall reaction thermodynamics are responsible for the lack of catalytic activity observed, with the solvation -corrected Gibbs free energy of the coupling reaction in question (i.e., CH2=CH2) + CO2- --> CH2=CHCO2H) calculated to be an unfavorable +42.7 kJ mol(-1).